Diseño y construcción de un fotorreactor anular concéntrico. Realización de ensayos de fotocatálisis heterogénea utilizando como contaminantes modelo cromo hexavalente y 4-clorofenol - Dwojak, Anabela Natalia (2026)
One of the greatest challenges in Heterogeneous Photocatalysis process for water treatment is to obtain immobilized photocatalyst with a high surface area and good photocatalytic activity, combined with suitable mechanical properties, in order to avoid the catalyst separation and recovery steps. In this paper, nanotubular TiO₂ coatings were synthesized by anodic oxidation on commercially pure titanium rings. The TiO₂-coated rings were fully characterized and used within a concentric annular modular photoreactor, constructed with commercial glass and Teflon, irradiated with a UVA fluorescent lamp (max = 365 nm) and operated in closed-loop recirculation mode. The paper also details the design and construction of the photoreactor, as well as the photocatalytic activity of the immobilized nanostructured TiO₂ photocatalysts in both oxidation and reduction model systems: 4-chlorophenol (4-CP) and Cr(VI), respectively, achieving 50% 4-CP and 100% Cr(VI) removal in 180 minutes, following a pseudo-first-order kinetics. The TiO₂-coated Ti rings displayed similar morphology, crystallinity, optical properties, and photocatalytic performance to previously synthesized TiO2-coated Ti plates, confirming the robustness, reproducibility, and scalability of the anodic synthesis technique, regardless of substrate geometry, and demonstrating the feasibility of using TiO₂ nanotubular coatings in scalable photoreactors for both oxidative and reductive processes for sustainable water treatment devices.